L-Selectin Enhanced T Cells Improve the Efficacy of Cancer Immunotherapy - Watson, H. Angharad; Durairaj, Ruban R. P.; Ohme, Julia; Alatsatianos, Markella; Almutairi, Hanan; Mohammed, Rebar N.; Vigar, Miriam; Reed, Sophie G.; Paisey, Stephen J.; Marshall, Christopher; Gallimore, Awen; Ager, Ann (Frontiers in Immunology, 2019)
The homing molecule, L-selectin (CD62L), is commonly used as a T cell activation marker, since expression is downregulated following engagement of the T cell receptor. Studies in mice have shown that CD62L+ central memory T cells are better at controlling tumor growth than CD62L− effector memory T cells, while L-selectin knockout T cells are poor at controlling tumor growth. Here, we test the hypothesis that T cells expressing genetically modified forms of L-selectin that are maintained following T cell activation (L-selectin enhanced T cells) are better at controlling tumor growth than wild type T cells. Using mouse models of adoptive cell therapy, we show that L-selectin enhancement improves the efficacy of CD8+ T cells in controlling solid and disseminated tumor growth. L-selectin knockout T cells had no effect. Checkpoint blockade inhibitors synergized with wild type and L-selectin enhanced T cells but had no effect in the absence of T cell transfers. Reduced tumor growth by L-selectin enhanced T cells correlated with increased frequency of CD8+ tumor infiltrating T cells 21 days after commencing therapy. Longitudinal tracking of Zirconium-89 (89Zr) labeled T cells using PET-CT showed that transferred T cells localize to tumors within 1 h and accumulate over the following 7 days. L-selectin did not promote T cell homing to tumors within 18 h of transfer, however the early activation marker CD69 was upregulated on L-selectin positive but not L-selectin knockout T cells. L-selectin positive and L-selectin knockout T cells homed equally well to tumor-draining lymph nodes and spleens. CD69 expression was upregulated on both L-selectin positive and L-selectin knockout T cells but was significantly higher on L-selectin expressing T cells, particularly in the spleen. Clonal expansion of isolated L-selectin enhanced T cells was slower, and L-selectin was linked to expression of proliferation marker Ki67. Together these findings demonstrate that maintaining L-selectin expression on tumor-specific T cells offers an advantage in mouse models of cancer immunotherapy. The beneficial role of L-selectin is unrelated to its' well-known role in T cell homing and, instead, linked to activation of therapeutic T cells inside tumors. These findings suggest that L-selectin may benefit clinical applications in T cell selection for cancer therapy and for modifying CAR-T cells to broaden their clinical scope.